2011
DOI: 10.1371/journal.pone.0027752
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an Alcohol Intervention Programme for TB Patients with Alcohol Use Disorder (AUD) - A Qualitative Study from Chennai, South India

Abstract: BackgroundThe negative influences of alcohol on TB management with regard to delays in seeking care as well as non compliance for treatment has been well documented. This study is part of a larger study on the prevalence of AUD (Alcohol Use Disorder) among TB patients which revealed that almost a quarter of TB patients who consumed alcohol could be classified as those who had AUD. However there is dearth of any effective alcohol intervention programme for TB patients with Alcohol Use Disorder (AUD).Methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…This is in line with our findings. Similar to Thomas et al [41], who performed a qualitative study of TB patients with alcohol problems, we found alcohol abuse to be a risk factor for delayed tuberculosis diagnosis. Further, alcohol is often related to a low level of social position and peer pressure plays a huge role in alcohol intake.…”
Section: Discussionsupporting
confidence: 87%
“…This is in line with our findings. Similar to Thomas et al [41], who performed a qualitative study of TB patients with alcohol problems, we found alcohol abuse to be a risk factor for delayed tuberculosis diagnosis. Further, alcohol is often related to a low level of social position and peer pressure plays a huge role in alcohol intake.…”
Section: Discussionsupporting
confidence: 87%
“…20,21 A recent study that assessed the feasibility of integrated alcoholism-tuberculosis treatment and care suggested the immediate need in India. 22 Adverse Drug Reactions (ADR) is known risk factors for treatment interruption and default from TB treatment. [23][24][25] Frequently reported minor side effects could be dealt with proper instructions on drug consumption, reassurance to patients and prompt symptomatic treatment before it leads to default.…”
Section: Discussionmentioning
confidence: 99%
“…This program in Tomsk, Russia, increased the proportion of favorable tuberculosis treatment outcomes among persons with a history of attempting to abstain from drinking alcohol by 18% (33). Although it is unclear if this approach would be effective in other communities, a recent study that assessed the feasibility of integrated alcoholism–tuberculosis treatment and care suggested the immediate need in India (34). It has been suggested that national tuberculosis programs, such as the Revised National Tuberculosis Control Program, could provide the infrastructure for an integrative approach where specialized alcoholism treatment services are almost nonexistent in the public sector (32).…”
Section: Discussionmentioning
confidence: 99%